Competitive asymmetries, birthing asynchrony and sibling rivalry in a social lizard - Alix Bouffet-Halle; Erik Wapstra; Geoffrey M. While (Behavioral Ecology and Sociobiology, 2024)
Family life often involves interactions between individuals who have different fitness goals, leading to conflict. Resolution of this conflict is key for the stabilisation of family life. Here, we used a lizard, Liopholis whitii , that lives in facultative family groups to characterise the nature and extent of sibling conflict and test the role that individual and litter characteristics play in shaping conflict between family members. We found significant variation in conflict between family groups, specifically in relation to siblings. In approximately half of the litters, siblings were aggressive towards one another, while in the other half of litters, there was no aggression observed between siblings. There were no differences between aggressive and non-aggressive litters in the key factors predicted to mediate conflict, including sex, offspring size, or litter size. However, in aggressive litters, the maximum amount of within-litter conflict decreased with an increase in the spread between births of siblings. First-born offspring were significantly more likely to be aggressive towards their siblings compared to second and third born offspring. While one offspring was usually the target of that aggression, we found no evidence that any individual-level factor predicted who received aggression. In aggressive litters, aggressive offspring spent a greater amount of time with their mother compared to non-aggressive offspring. Similar asymmetries in the amount of time offspring spent with their mother between siblings were also observed in non-aggressive litters. Combined, our results suggest that birth order is the main driver of sibling conflict in aggressive litters in this facultatively social lizard species, suggesting that birthing asynchrony may provide females with a mechanism to manage conflict. Significance statement Conflict is a ubiquitous aspect of family life; it occurs between adults, between parents and offspring as well as between siblings. We show that the extent of conflict between siblings varies considerably within and between families in a lizard that exhibits prolonged associations between parents and offspring. We found no effects of offspring sex or size on within or between litter conflict. Instead, the number of days that passed between the birth of offspring appears to be the main factor that influences how much conflict there is between siblings. Furthermore, birth order was the main factor predicting which offspring was dominant. Combined this suggests that birthing asynchrony, the ability of females to spread out births across multiple days, may play a crucial role in the management of conflict in this system. As the moderation of conflict is crucial for the stabilisation of family life, these results provide important insights into the early evolution of social life.